Outcast - Allston, Aaron (New York : Ballantine Books, 2009)
In the first book of the Star Wars: Fate of the Jedi series, listeners experience the Galactic Alliance in crisis after a violent civil war and the fall of Darth Caedus. As prominent leaders gather for a crucial summit at Coruscant, the future of the Jedi remains uncertain. When Chief of State Natasi Daala and the media stir up mass anti-Jedi sentiments, Luke and his son Ben go rogue and investigate Jacen Solo's corruption and downfall, uncovering startling secrets within the Force
New York Times Bestseller
Keywords: Science Fiction; Organa, Leia (Fictitious character); Star Wars fiction